Buraku, Capitalism and the State in Japan - Kobayakawa, Akira, (Social Sciences E-Books Online, Collection 2026., 2026)
Applying universal themes, this book analyses the discrimination faced by and the (re)construction of the Buraku people during Japan's modernization. State and capital have created the ongoing plight of the Buraku. This book demonstrates that Buraku discrimination has been a springboard for domination, both during and after Japan's colonial rule in Asia and has been an important function of governance in Japan. Buraku discrimination is reproduced in both cities and towns, forcing many Buraku people to suffer silently. To combat this situation, there are Buraku resistance movements, studied in depth here.